Comparative efficacy and safety of infliximab and vedolizumab therapy in patients with inflammatory bowel disease: a systematic review and meta-analysis - Peyrin-Biroulet, Laurent; Arkkila, Perttu; Armuzzi, Alessandro; Danese, Silvio; Guardiola, Jordi; Jahnsen, Jørgen; Lees, Charles; Louis, Edouard; Lukáš, Milan; Reinisch, Walter; Roblin, Xavier; Jang, Minyoung; et al. (BMC gastroenterology, 2022)
BACKGROUND AND AIMS: There are limited comparative data for infliximab and vedolizumab in inflammatory bowel disease patients. METHODS: We conducted a systematic review and meta-analysis to compare the efficacy and safety of infliximab and vedolizumab in adult patients with moderate-to-severe Crohn's disease or ulcerative colitis. RESULTS: We identified six eligible Crohn's disease and seven eligible ulcerative colitis trials that randomised over 1900 participants per disease cohort to infliximab or vedolizumab. In the Crohn's disease and ulcerative colitis cohorts, infliximab yielded better efficacy than vedolizumab for all analysed outcomes (CDAI-70, CDAI-100 responses, and clinical remission for Crohn's disease and clinical response and clinical remission for ulcerative colitis) during the induction phase, with non-overlapping 95% confidence intervals. In the maintenance phase, similar proportions of infliximab- or vedolizumab-treated patients achieved clinical response, clinical remission, or mucosal healing in both Crohn's disease and ulcerative colitis. For the safety outcomes, rates of adverse events, serious adverse events, and discontinuations due to adverse events were similar in infliximab- and vedolizumab-treated patients in both diseases. The infection rate was higher in infliximab for Crohn's disease and higher in vedolizumab when treating patients with ulcerative colitis. There was no difference between the treatments in the proportions of patients who reported serious infections in both indications. CONCLUSIONS: Indirect comparison of infliximab and vedolizumab trials in adult patients with moderate-to severe Crohn's disease or ulcerative colitis demonstrated that infliximab has better efficacy in the induction phase and comparable efficacy during the maintenance phase and overall safety profile compared to vedolizumab.
Keywords: ulcerózní kolitida; Crohn Disease; gastrointestinální látky; Tumor Necrosis Factor-alpha; Infliximab; Inflammatory Bowel Diseases; Monoclonal; Crohnova nemoc; Adult; dospělí; Ulcerative colitis; Gastrointestinal Agents; Biological therapy; idiopatické střevní záněty; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Antibodies; lidé; Humans; infliximab; Colitis, Ulcerative; IBD; Crohn’s disease